ECONOMIC LIBERALIZATION, THE INFORMAL SECTOR, AND URBAN UNEMPLOYMENT: A THEORETICAL ANALYSIS. Issue 3 (19th December 2018) - Ghosh, Sujata; Mandal, Biswajit; Gupta, Kausik
Abstract : In this paper, we construct a three‐sector general equilibrium model of a small open economy with an informal sector and examine the impact of a less protectionist policy on output levels, factor prices, and the level of urban employment. We show that the urban unemployment rate has reduced with the contraction of an import‐competing manufacturing sector consequent upon tariff reductions. The informal intermediate sector has contracted as well. A possibility to expand the exportable agricultural sector exists, with an increased wage rate. Our analysis is then extended to introduce foreign capital inflow and examine the output effects and the level of unemployment. Interestingly, in the extended model, urban unemployment is aggravated as a result of an inflow of foreign capital.